Predictors of free sugars intake trajectories across early childhood – results from the SMILE birth cohort study - Bell, L.K.; Nguyen, H.V.; Ha, D.H.; Devenish-Coleman, G.; Golley, R.K.; Do, L.G.; Scott, Jane (MDPI AG, 2024)
Foods and beverages high in free sugars can displace healthier choices and increase the risk of weight gain, dental caries, and noncommunicable diseases. Little is known about the intake of free sugars across early childhood. This study aimed to examine the longitudinal intake from 1 to 5 years of free sugars and identify the independent maternal and child-related predictors of intake in a cohort of Australian children participating in the Study of Mothers’ and Infants’ Life Events Affecting Oral Health (SMILE). Free sugars intake (FSI) was previously estimated at 1, 2, and 5 years of age, and three distinct FSI trajectories were determined using group-based trajectory modelling analysis. This study utilized multinomial logistic regression to identify the maternal and child-related predictors of the trajectories. The risk of following the ‘high and increasing’ trajectory of FSI compared to the ‘low and fast increasing’ trajectory was inversely associated with socio-economic disadvantage (aRRR 0.83; 95% CI 0.75–0.92; p < 0.001), lower for females (aRRR 0.56; 95% CI 0.32–0.98; p = 0.042), and higher in children with two or more older siblings at birth (aRRR 2.32; 95% CI 0.99–5.42; p = 0.052). Differences in trajectories of FSI were evident from an early age and a high trajectory of FSI was associated primarily with socio-economic disadvantage, providing another example of diet quality following a social gradient.